Imaging Reactive Oxygen Species-Induced Modifications in Living Systems - YALÇIN, AHMET SUHA (MARY ANN LIEBERT, INC, 2016)
Significance: Reactive Oxygen Species (ROS) may regulate signaling, ion channels, transcription factors, and biosynthetic processes. ROS-related diseases can be due to either a shortage or an excess of ROS. Recent Advances: Since the biological activity of ROS depends on not only concentration but also spatiotemporal distribution, real-time imaging of ROS, possibly in vivo, has become a need for scientists, with potential for clinical translation. New imaging techniques as well as new contrast agents in clinically established modalities were developed in the previous decade. Critical Issues: An ideal imaging technique should determine ROS changes with high spatio-temporal resolution, detect physiologically relevant variations in ROS concentration, and provide specificity toward different redox couples. Furthermore, for in vivo applications, bioavailability of sensors, tissue penetration, and a high signal-to-noise ratio are additional requirements to be satisfied. Future Directions: None of the presented techniques fulfill all requirements for clinical translation. The obvious way forward is to incorporate anatomical and functional imaging into a common hybrid-imaging platform.
Keywords: IN-VIVO EPR; 2-PHOTON FLUORESCENT-PROBE; FREE-RADICAL REACTIONS; REDOX STATUS; OXIDATIVE STRESS; NITRIC-OXIDE; HYDROGEN-PEROXIDE; LIVE CELLS; MULTIPHOTON MICROSCOPY; NONINVASIVE ASSESSMENT